Implementation of Design Thinking in Interactive Prototype Branding and Activation at Soekarno-Hatta Airport - Prameswari, Alifah Lintang; Dianty, Amelia Putri; Andayani, Pratiwi (Politeknik Siber Cerdika Internasional, 2025)
This research aims to explore the application of Design Thinking in designing an interactive prototype based on artificial intelligence (AI) for branding and activation needs at Soekarno-Hatta International Airport. Utilizing a creative and human-centered approach, this study collects data through observations, interviews, and surveys to understand passengers' behavior and perception of interactive branding media. The results show that the AI Device + Machine concept is the most potential alternative to SPG Mobile, mascot activation, and specific expertise activation because it excels in brand message consistency, operational efficiency, and its ability to deliver personalized and adaptive interactions in real time. In addition to being able to operate indefinitely and collect evaluative data, this concept also strengthens the airport's innovative image. However, challenges in the form of high initial costs, technical risks, and limitations of emotional proximity still need to be considered in its implementation. The implications of this research provide strategic guidance for airport management and brand partners in optimizing passenger engagement through technology-driven experiential branding, while also contributing to the theoretical understanding of Design Thinking application in complex public service environments. This study offers practical frameworks for balancing technological innovation with human-centered design principles in developing sustainable and scalable branding solutions for large-scale transportation hubs.